Buddhisme dan Budaya Lokal - Sril Lestari (STABN Sriwjaya, 2023)
Religion cannot be separated from the culture in which it develops. This study uses discourse analysis about Buddhism and local culture. The method used in this study is Discourse Analysis. Namely a study methodology that focuses on the use of texts used in social and cultural contexts to communicate meaning. In the study